1997
DOI: 10.1177/002215549704500810
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical Localization of Ouabain-sensitive, K+-dependentp-nitrophenylphosphatase Activity in the Facial Nerve of Reserpinized Guinea Pigs

Abstract: SUMMARY Ion-transporting Na,K-ATPase plays an essential role in nerve conduction. To clarify the cytochemical effects of reserpine on transport Na,K-ATPase activity, the localization of ouabain-sensitive, K ϩ -dependent p -nitrophenylphosphatase (K-NPPase) activity was investigated in the facial nerves of normal and reserpinized guinea pigs using a ceriumbased method. In the normal facial nerve, the reaction product of K-NPPase activity was observed on the internodal axolemma and Schmidt-Lanterman incisures. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Pollay et al (1985) showed that ouabain almost completely inhibited choroidal Na,K-ATPase activity and decreased CSF formation by 70-80%. The present experimental results also demonstrated that choroidal K-NPPase activity was greatly decreased from Day 3 to Day 7 after reserpine administration, which was similar to the strial (Kanoh et al 1993;Kanoh 1994) and facial nerve K-NPPase activity (Kanoh 1997). Because high doses of reserpine induced the depletion of catecholamines, these results indicate that catecholamines may be essential for the regulation and mainte-nance of normal choroidal Na,K-ATPase activity and CSF production.…”
Section: Abstract K-nppase Cytochemistrysupporting
confidence: 78%
See 1 more Smart Citation
“…Pollay et al (1985) showed that ouabain almost completely inhibited choroidal Na,K-ATPase activity and decreased CSF formation by 70-80%. The present experimental results also demonstrated that choroidal K-NPPase activity was greatly decreased from Day 3 to Day 7 after reserpine administration, which was similar to the strial (Kanoh et al 1993;Kanoh 1994) and facial nerve K-NPPase activity (Kanoh 1997). Because high doses of reserpine induced the depletion of catecholamines, these results indicate that catecholamines may be essential for the regulation and mainte-nance of normal choroidal Na,K-ATPase activity and CSF production.…”
Section: Abstract K-nppase Cytochemistrysupporting
confidence: 78%
“…Using a cerium-based method (Kobayashi et al 1987), Kanoh et al (1993) and Kanoh (1994) determined the cytochemical localization of ouabain-sensitive, K ϩ -dependent, p -nitrophenylphosphatase (K-NPPase) activity in strial marginal cells after reserpine administration and found that the enzyme activity was undetectable. Kanoh (1997) also investigated the cytochemical localization of K-NPPase activity in the reserpinized facial nerve and reported that the reaction product was undetectable on the internodal axolemma. The aim of the present study was to determine if there are any changes in K-NPPase activity in the choroid plexus after reserpine administration.…”
mentioning
confidence: 99%
“…The dose of reserpine used in the present study (10 mg/kg) was thought to be high enough to completely abolish catecholamine activity. In previous studies, transporting Na + /K + -ATPase activity on the internodal axolemma of the guinea pig facial nerve was found to be decreased after reserpine administration, 18 and the potassium concentration of the cochlear endolymph was found to be decreased at 24 hours after reserpine administration. 4 These results indicated that catecholamines might be essential to maintaining normal Na + /K + -ATPase activity.…”
Section: Resultsmentioning
confidence: 86%